Pelindungan Merek Terhadap Dilusi Merek Dalam Ruang Virtual Metaverse Berdasarkan Perjanjian Syarat Dan Ketentuan Pengguna Akun Metaverse - Azrinda Rachmadanty Zahra; Rika Ratna Permata; Tasya Safiranita Ramli (Deposisi: Jurnal Publikasi Ilmu Hukum, 2023)
The development of technology today makes humans coexist with technology. Many human activities can be carried out through the internet network. One of them is the presence of the metaverse which is a technology that contains virtual interactions, digital objects, and decentralized humans from various platforms. Metaverse is used by many people as a medium for buying and selling transactions. Metaverse users generally sell their products in the form of NFTs. Various well-known brands have started promoting their products through the metaverse. The emergence of well-known brands in the metaverse is an opportunity for irresponsible parties to infringe brand rights. As was the case in Ryder Ripps v. Yuga Labs. Pollution, imitation, obscuration, and so forth of well-known trademarks are carried out by irresponsible parties. One of them is the doctrine of Trademark Dilution. Trademark dilution is the unauthorized use by other parties that can weaken the quality or characteristics of a trademark. This makes the question of how the protection of trademarks in the virtual space of the metaverse and what legal action can be taken when there is a violation of trademark rights. Not many countries have regulated the protection of digital trademarks specifically against trademark dilution, as well as Indonesia. This research will be conducted using a non-native juridical approach method with legal sources in the form of laws and regulations, international agreements, theories, and legal rules. The focus of this research is how metaverse with the platform in it can protect the trademark with the terms and conditions agreement of account users in the platform. The result of this research is that brands can be protected against infringement of rights to the brand as well as brand dilution by referring to the terms and conditions of account users listed in the platform. In addition, the legal action that can be taken is to file a lawsuit as determined by the platform and the removal of related content.